Assessment of rural agro-based tourism operation: case study of clustered homestays in Kelantan, Malaysia - Hafizah Hasbullah (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2020)
Tourism plays a vital role in Malaysia as one of the most significant contributors to the national economy, contributing a total of RM 190.3 billion (13.3%) of Gross Domestic Product (GDP) in 2018 (World Travel and Tourism Council, 2019). Agro-tourism is one of the tourism concept that is rapidly gaining popularity in Malaysia as it offers tourists different type of activities relating to the agriculture sector. The local community would offer a homestay program as one of the activities for the visitors. Homestay programmes provided opportunities where visitors can discover more of local agro-tourism practices and cultural activities. Tucked away in north-eastern Peninsular Malaysia and bounded by Thailand in the north, Terengganu in the east, Pahang in the south and Perak in the west, Kelantan has successfully continued legacy of keeping alive its rich tangible (handicraft, historical sites and buildings) and intangible heritage (culture, customs and traditions). Kelantan is full of natural resources. Even though Kelantan has a vast number of tourist products and attractions, there is still a lack of studies and information on Homestays in Kelantan. The main purpose of this study is to fill in the gap by providing detailed information on homestay programme in Kelantan area. This study also sought to: (1) take inventory of facilities and amenities in the study area; (2) analyse skills (soft-infrastructure) perceived to be essential by homestay owners; and (3) propose possible approaches or recommendations that could upgrade infrastructure for tourist conveniences. Research methodology using a content analysis approach was adopted in order to review documented sources and a qualitative approach using face to face interview with the homestay owners. The study revealed the assessment of rural agro-tourism and local community income generated from Homestays in Kelantan. The results showed that despite the excellent efforts in maintaining the condition of their rooms to offer and rental rates per night had been relatively competitive, and they still received a low number of tourists every year. During the discussion session also, homestay owners were expressing their expectation in enhancing their interpersonal skills.